Prevalence, indications, and outcomes of operative vaginal deliveries among mothers who gave birth in Ethiopia: A systematic review and meta-analysis - Balis, Bikila; Debella, Adera; Ketema, Indeshaw; Eshetu, Bajrond; Zerihun, Ebisa; Deressa Wayesa, Alemayehu; Habte, Sisay; Alemu, Adisu; Bekele, Habtamu (Frontiers in Global Women's Health, 2022)
Background: Operative vaginal deliveries represent an alternative to address problems during the second stage of labor. Obstetricians have access to two different instruments obstetrics forceps and vacuum which should be conducted with indication. Understanding the pooled prevalence of OVDs, its indications, and their outcomes would help concerned stakeholders to make evidence-based decisions in adopting suitable measures to reduce OVDs-related maternal and neonatal complications. This systematic review and meta-analysis aimed to determine the prevalence, indications, and outcomes of operative vaginal deliveries among mothers who gave birth in Ethiopia. Methods: Databases such as PubMed, SCOPUS, Web of Sciences, CAB Abstract, EMBASE, and CINHAL (EBSCO) were used to search studies that have been conducted in Ethiopia. Relevant sources were consulted to retrieve unpublished studies. All cross-sectional studies were included. Studies were independently assessed for inclusion, data extraction, and risk of bias. Results: A total of twelve cross-sectional primary studies with a sample size of 3,245 were used to determine the pooled prevalence of operative vaginal delivery among mothers who gave birth in Ethiopia. The overall pooled prevalence of operative vaginal delivery among mothers who gave birth in Ethiopia was 10% (95% CI: 8 to 13) with I2 = 98.82% and a p-value ≤ 0.001. Fetal distress, prolonged labor, and maternal exhaustion were the most common feto-maternal indications of OVDs whereas; neonatal death, poor Apgar score, admission to neonatal intensive care unit, perianal tear, and postpartum hemorrhage were complications that occur following the OVDs in Ethiopia. Conclusion: This systematic review and meta-analysis showed ten out of a hundred mothers undergo operative vaginal deliveries. Almost all feto-maternal complications that arise following OVDs were preventable with special training and adherence to instrumental delivery protocol.